Thermophysical properties of Copper/Water nanofluid for automotive cooling system – Mathematical modeling - S.A, Fadhilah; I., Hidayah; M.Z, Hilwa; H.N , Faizah; R.S, Marhamah (Fakulti Kejuruteraan Mekanikal (FKM), Universiti Teknikal Malaysia Melaka (UTeM), 2013)
Nanofluid is an advanced fluid with enhanced thermophysical properties that has been introduced in many applications for better heat transfer process. In automotive cooling system, conventional coolants such as water and ethylene glycol could have superior thermophysical properties of thermal conductivity, viscosity, density and heat transfer coefficient by introducing nanoparticles suspension. This study investigated the thermophysical properties of Copper/Water nanofluid by using mathematical modeling approach to come out with a new coolant for Louvered-fins and flat tube of a radiator. The nanofluid showed enhanced thermophysical properties with nanoparticles suspension of 2 vol.% to 10 vol.%. By offering 10 % of copper nanoparticles concentration, the heat transfer coefficient of the nanofluid was increased up to 26000 W.m-2K-1 with enhancement of 92 %. Consequently, it also enhanced the heat transfer rate in the cooling system. The different particles sizes of 10 nm, 50 nm, and 100 nm showed different heat transfer coefficients but the heat transfer rate in the radiator is similar, up to 64400 W with 10 % of nanoparticle volume fraction. The nanofluids showed better heat transfer characteristics as a new alternative coolant for the radiator.